2008
DOI: 10.1016/j.brainres.2008.05.086
|View full text |Cite
|
Sign up to set email alerts
|

Brain-derived neurotrophic factor modulates expression of chemokine receptors in the brain

Abstract: Chemokine receptors, and in particular CXCR4 and CCR5 play a key role in the neuropathogenesis of Human Immunodeficiency Virus-1 (HIV)4 associated dementia (HAD). Thus, new insight into the expression of CXCR4 in the central nervous system may help develop therapeutic compounds against HAD. Brain-derived neurotrophic factor (BDNF) is neuroprotective in vitro against two strains of the HIV envelope protein gp120 that binds to CXCR4 or CCR5. Therefore, we examined whether BDNF modulates chemokine receptor expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 53 publications
4
27
0
Order By: Relevance
“…BDNF is a neurotrophic factor that has been shown to prevent DA loss in animal models of PD (Hyman et al 1991;Altar et al 1992), and to block the neurotoxic effect of CXCR4 agonists (Bachis and Mocchetti 2005;Nosheny et al 2007). Indeed, it has been demonstrated that BDNF reduces the expression of neuronal CXCR4 in vivo Ahmed et al 2008). These data depict a scenario in which DA neurons in the SN may be spared from apoptosis if pro-inflammatory cytokines/chemokines levels are balanced by a sufficient amount of neurotrophic factors.…”
Section: Discussionmentioning
confidence: 96%
“…BDNF is a neurotrophic factor that has been shown to prevent DA loss in animal models of PD (Hyman et al 1991;Altar et al 1992), and to block the neurotoxic effect of CXCR4 agonists (Bachis and Mocchetti 2005;Nosheny et al 2007). Indeed, it has been demonstrated that BDNF reduces the expression of neuronal CXCR4 in vivo Ahmed et al 2008). These data depict a scenario in which DA neurons in the SN may be spared from apoptosis if pro-inflammatory cytokines/chemokines levels are balanced by a sufficient amount of neurotrophic factors.…”
Section: Discussionmentioning
confidence: 96%
“…They included two SNPs within the CCL3 (rs1719134 and rs1130371)(Levine 2009), a three-SNP haplotype within the MBL-2 gene (rs1800450, rs1800451, and rs5030737)(Spector et al), and single SNPs within coding or non-coding regions of the CCL2 gene (rs1024611)(Gonzalez et al 2002), TNF-α (rs1800629)(Mathis et al 2008), COMT (rs4680)(Bousman et al 2010, Kumar et al 2011), BDNF (rs6265)(Ahmed et al 2008, Nosheny et al 2007), DBH (rs1611115)(Kumar et al 2011), DR2/ANKK1 - rs1800497)(Kumar et al 2011), DR3 (rs6280), and CXCL12 (rs1801157)(Langford et al 2002, Peng et al 2006). …”
Section: Methodsmentioning
confidence: 99%
“…Neurotoxic actions of viral proteins include an increase in the production of pro-inflammatory cytokines and a reduction of anti-apoptotic neurotrophic factors, such as BDNF and glial-cell derived neurotrophic factor (Nosheny et al, 2006) . Reduction of BDNF culminates in an up-regulation of CXCR4 and CCR5 (Nosheny et al, 2004; Ahmed et al, 2008; Avdoshina et al, 2011), two HIV co-receptors that also promote neuronal apoptosis. In addition, BDNF promotes adult neurogenesis (Li et al, 2008) that is believed to be essential for specific cognitive functions that decline in HIV positive subjects (Venkatesan et al, 2007).…”
Section: Introductionmentioning
confidence: 99%